Pengembangan Sistem Informasi Manajemen untuk Penilaian Siswa SD Al Islah Surabaya - Yunanto, Andhik Ampuh; Prasetyo, Edy Eko; Mubarok, Akhmad Romdhoni; Kusumaningtyas, Amalia; Bitafsaji, Ashitak Marchi (Teknik Informatika Universitas Pamulang, 2021)
In the world of education, the use of information and communication technology offers an enormous number of opportunities. One of the potential benefits of information and communication technology for education is to support the organization and management of learning. One of the organizations in Indonesia that does not utilize a management system is school institutions, especially elementary schools. SD Al Islah Surabaya in recording student grades using manual methods. Although it did not cause problems, this method of recording was deemed ineffective and inefficient. The purpose of developing this application is to make it easier for teachers to make assessments and minimize errors in inputting values and streamline the work of teachers. The desired result is the creation of a website-based application in which there are features for organizing student grades. In this study, the test results show that the application built has good performance. And the target user also gives a positive value to this application. So that the development of this application can be concluded that the application can be accepted by users and can improve performance effectively and efficiently